SISTEM INFORMASI PAROKI SANTO PIUS X AEK KANOPAN BERBASIS WEB - Pakpahan, Sorang; Naibaho, Yeti (STMIK KAPUTAMA, 2019)
Information systems are understood as a collection of subsystems that are interconnected, gather together and form a single unit, interact and work together between one part and another in certain ways to perform data processing functions, receive input data, then process it, and produce output in the form of information. The church is an association, association, or fellowship for Christians in one faith that is shaded in a container of organizations or existing religious institutions that have been acknowledged by the government Parish data processing at this time is still manual such as processing data on independent funds, pastor's journey to the station or environment, scheduling Misa is still manual so that people have to come to Parish. To overcome the problems faced by the Aek Kanopan parish at this time, it is expected that with the parish pastoral information system which can later be carried out computerized systems can even be presented in the form of a website.